A2.04 The role of somatic hypermutation and n-glycosylation in the anti-nets immunoreactivity of ra synovial monoclonal antibodies. (24th February 2016) - Corsiero, E; Carlotti, E; Prediletto, E; Jagemann, L; Pitzalis, C; Bombardieri, M
Abstract : Background and objectives: We previously showed that anti-citrullinated peptide/protein antibodies (ACPA) targeting citrullinated antigens contained in neutrophils extracellular traps (NETs) can be manufactured within ectopic germinal centre-like structure (GC-LS) in the rheumatoid arthritis (RA) synovium. Here, we aimed to characterise a) whether the RA synovial anti-NETs antibodies had undergone antigen-driven affinity maturation, b) the importance of somatic hypermutations (SHM) within the VH/VL chain for their binding and c) whether the presence of N-glycosylation sites in the Fab domains introduced by SHM can modulate the reactivity towards NETs. Materials and methods: 82 full recombinant monoclonal antibodies (RA-syn-rmAbs) were generated from single CD19 + B-cells FACS-sorted from fresh GC-LS+ synovial cell suspensions following IgVH+VL genes cloning. RA-syn-rmAbs for reversion experiments (n = 9) were chosen according to their level of reactivity towards NETs. N-glycosylation sites (N-x-S/T) in the Fab domains were predicted using the NetNGlyc1.0 Server and the presence of glycans was detected by total glycoprotein staining on gel. Reversion of the IgV genes into germ-line (GL), generation of hybrid clones (where VH/VL or selected CDRs/FRs were reverted into GL, n = 5) and N-glycosylation mutants (where asparagine (N) was substituted with glutamine (Q), n = 7) was performed by overlap-PCR. Anti-NETs immunoreactivity was detected using cell-based immunoassays with activated peripheral blood or RA synovial fluid neutrophils. Results: The RA-syn-rmAbs anti-NETs immunoreactivity was dependent on affinity maturation within GC-LS and was completely abrogated when the full IgVH+VL genes were reverted to GL. Similarly, when only the single IgVH/VL gene was reverted to GL, the reactivity towards NETs was lost suggesting that both VH+L chains are important in conferring the reactivity towards NETs. Moreover, the increased molecular weight observed in selected anti-NET antibodies was dependent on the presence of Fab-linked glycans and was lost in the GL counterpart. Conclusions: Importantly, our data showed that SHM is necessary for the development of high-affinity NETs-binding antibodies in synovial GC-LS and for the introduction of N-glycosylation sites in the Fab domain which could influence the NET-antigens binding. Defining the contribution of individual CDRs and FRs to the affinity of antigen-binding sites may help to engineer new therapeutic Abs and design of CDRs/FRs-specific peptides for tolerogenic strategy.